"Almost Looks Illegal": Family Dick's Daddy's Little Boy Gay Pornography Series and Its Too-Young Look. Issue 9 (29th July 2022) - Brennan, Joseph
ABSTRACT: Family Dick is a commercial gay pornography website that has courted controversy for both its stepfather-son theme and for the youthful stylings of its Daddy's Little Boy series. This article reads viewer commentary (selected from more than 700 comments) of scenes within the series posted to its Pornhub channel. Textual analysis is employed to read the series itself and its distinctive esthetic, which logically leads to discussion of views on the too-young "look" of the series and the use of certain "legislative language" by those who deem the content to be potentially unlawful. The article also considers the implications resultant from the range of views presented in the discourse and a tendency for the series to inspire viewers to reflect on personal experiences and desires. As the first study of its kind, it ends by nominating a range of future research directions.